High-grade serous ovarian carcinoma in a patient with end-stage renal disease - Gajić, Selena; Džamić, Vanja; Bontić, Ana; Petrović, Kristina; Kezić, Aleksandra (Vojnosanitetski pregled, 2024)
Introduction. Ovarian carcinoma, being one of the most common gynecologic cancers, has the highest mortality rate. The gold standard for the treatment of patients with advanced ovarian carcinoma, along with angiogenesis inhibitors applied in certain advanced stages, is cytoreductive surgery, followed by chemotherapy (CHT). The use of chemotherapeutic agents in hemodialysis (HD) patients has some specificities and limitations, and no CHT guidelines exist for treating those patients. Case report. We present a 45-year-old female patient with end-stage renal disease undergoing HD treatment. Abdominal and pelvic magnetic resonance imaging showed a multicystic mass with a total diameter of 93 × 115 × 168 mm in the right ovary and two subcapsular lesions in the VI segment of the liver with a diameter of 22 × 14 mm and 9 mm (stage IVb ovarian cancer). The serum level of the tumor marker cancer antigen 125 (CA-125) was 93 U/mL. A total hysterectomy with bilateral salpingo-oophorectomy and infracolic omentectomy was performed. Histopathological analysis of the surgical specimen confirmed high-grade serous ovarian adenocarcinoma, FIGO stage IVb. After surgery, she was treated with carboplatin and paclitaxel combination CHT, determining the dose of carboplatin according to the Calvert formula and initiating HD within 20 hrs of infusion. Two years after the diagnosis was made, the presented patient is in good condition. Conclusion. HD patients can be treated with a combination CHT regimen of carboplatin and paclitaxel, determining the dose of carboplatin according to the Calvert formula and initiating HD within 20 hrs from the end of the chemotherapeutic infusion.